Konsep Pendidikan Jerman dan Australia; Kajian Komparatif dan Aplikatif terhadap Mutu Pendidikan Indonesia - Isri, Saifullah; Saifullah Isri (Jurnal Pendidikan Islam, 2015)
AbstractEducation is always influenced by factors that enveloped it. So it is very likely to occur differences in product and quality of education between one institution and another institution or between one country to another. This difference initiates the researcher to be open-minded and examine the system and education implementation in an institution or another country in order to absorb positive information for improvement and advancement of education. This encourages the emergence of comparative education studies. Indonesia, in an effort to increase the quality of its education, needs to conduct a similar study by examining and comparing Indonesian education with other countries, in this case, Germany and Australia that their quality of education is among the best in the World.